Double-diffusive convection in an anisotropic porous layer using the Darcy–Brinkman–Forchheimer formulation (Archives of Mechanics - Test, 2018)
The aim of this paper is to discuss the double-diffusive natural convection in an anisotropic porous medium saturated with a binary fluid. The vertical walls of porous cavity are subjected to uniform temperature and concentration whereas the other surfaces are assumed to be adiabatic and impermeable. Darcy–Brinkman–Forchheimer model with the Boussinesq approximation was used to formulate the problem and the finite volume method was adopted to resolve the governing equations system. A parametric study was conducted and the results are presented and analyzed. They showed an excellent agreement in comparison with those reported in literature. They also allowed the evaluation of the control parameters effect on the flow structure, heat and mass transfer.